Aktionsart - ett problem i tvåspråkiga ordböcker - Martola, Nina (Nordiske Studier i Leksikografi, 2003)
In this article some problems falling under the conception of Aktionsart will be discussed. The Finnish language has a rich morphology and there are verb types that inherently express momentaneous, iterative and durative actions. In Swedish the Aktionsart is expressed mainly in other ways, not inherently in the verb. Lexicographers working on dictionaries between the two languages are supposed to handle the problems this fact causes. I have looked at two Finnish-Swedish/Swedish-Finnish dictionaries of middle size to see what the lexicographers have done to transfer the Finnish Aktionsart system into the Swedish and vice verse. Quite frequently the same equivalents are given for e.g. a momentaneous and a durative verb without any further explanations. Sometimes this is possible, since some of the Swedish verbs are quite neutral or inherently express two types of actions. But in many other cases it seems peculiar. The equivalents would need some kind of explanation. My conclusion is that the Aktionsart problem has been rather neglected, at least in dictionaries of this size.